IMPLEMENTATION OF CONTENT EDUCATION AT CTU TUBURAN CAMPUS, TUBURAN, CEBU: SOME PROPOSALS - Tanjusay, Bethel B.; Brigoli, Helen C.; Abaqueta, Maria Carly Y. (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 15 No. 1, 2012, 2012)
This study was made to assess the implementation of the course offering in the Bachelor of Elementary Education (BEED) curriculum major in Content Education (CE) and minor in Home Economics & Livelihood (HELE) at CTU Tuburan Campus. The descriptive method was employed using the prospectus of the BEED curriculum for document analysis and questionnaire with interview technique was administered to the respondents. In the First Year curriculum, the respondents perceived Ecology subject as most important while in the Second Year curriculum, they perceived Interactive English as most important; in the Third Year curriculum, Problem Solving was most important and in the Fourth Year curriculum Thinking Skills as most important subject. Respondents suggested that subjects as Research, Personnel Management & Supervision, Guidance Counseling, Statistics including Probability and Permutation be included in the curriculum as they considered them very useful and necessary in their teaching jobs. They considered Academic subjects needed a longer number of hours of instruction per week. The problems met by the respondents on subjects offered in the Content Education were the applicability of the subjects in the Elementary Level of instruction followed by high tuition Fees and repetition of topics It was recommended that Content Education subjects that are not applicable in the Elementary level of instruction be eliminated. Subjects as Research, Personnel Management & Supervision, Guidance Counseling, Statistics including Probability and Permutation be included in the Curriculum. Academic subjects be given longer number of hours of instruction per week. Some subjects be integrated with other subjects so that there will be no repetition of topics. And finally, a further study is recommended on other CTU campuses and other colleges and universities also implementing the same curricular offering.